الحركة الدعوية للمرأة في قسم الأرشاد النسوي بسلطنة عمان "دراسة تحليلية" - Houda Mohammed Al-Mamari
Over years, Omani women were playing an important role in community. They had their place in advocacy, fatwa and authoring making them enriching the community and contributing to the elevation of science. As an employee of Women's Guidance Department, we have primarily conduct an analytical study on this Department, state its impact and highlight its activities. we have pursued in this thesis the critical descriptive analytical method and used the questionnaire as a tool to collect information. Such information has been analyzed using(SPSS).The questionnaire has been distributed to three categories(Women's society, female employees and female administrators). we have come to the most important results which are: the availability of satisfaction among beneficiaries with the Department services in terms of improvement of services, good deal, rapidly processing a transaction, keeping up with modern technology in the delivery of services by the Department, the female guides’ need to increase the time of training programs as the results have shown the extent of the contribution of these programs in the development of the work field, the development of the spirit of creativity and change of the female guide’s direction to the better. It turns out also that the majority of the female guides cannot speak any languages other than Arabic. 55% of female administrators can speak languages other than Arabic. However, the Department is suffering from the lack of availability of financial resources, which slows down progress and the Department lacks to private sectors to hold events, which reduces the expansion of the Department. Researcher recommended giving female guides courses in various languages pointing out to the importance of financial resources and capabilities that enable the Department to enhance the level of advocacy and development, and to increase the opportunities to providing training programs on a regular basis to the female administrators and female employees.